2022
DOI: 10.3389/fevo.2022.1043976
|View full text |Cite
|
Sign up to set email alerts
|

Application of carbon emission prediction based on a combined neural algorithm in the control of coastal environmental pollution in China

Abstract: The marine ecosystem provides the environment, resources, and services necessary for the development of every human society. In recent years, China's coastal zone has been polluted to varying degrees, which has seriously affected its development. The characteristics of marine environmental data include the variety of data types, the complexity of factors affecting the marine environment, and the unpredictability of marine pollution. Currently, there are few studies applying the clustering analysis algorithm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The LMDI estimation can be utilized to compare a series of indices and discuss their effects on the trends during the period from the base year (zero) to the current year (1) [ 8 , 61 ]. Moreover, a study by Wang [ 66 ] found that this model can be used to predict environmental issues. For this purpose, the study applies the LMDI that permits the perfect disaggregation of variations into driving forces, whose contributions can be added to the overall utilization variation without residual terms.…”
Section: Methodsmentioning
confidence: 99%
“…The LMDI estimation can be utilized to compare a series of indices and discuss their effects on the trends during the period from the base year (zero) to the current year (1) [ 8 , 61 ]. Moreover, a study by Wang [ 66 ] found that this model can be used to predict environmental issues. For this purpose, the study applies the LMDI that permits the perfect disaggregation of variations into driving forces, whose contributions can be added to the overall utilization variation without residual terms.…”
Section: Methodsmentioning
confidence: 99%
“…Each neuron in the network has connections with other neurons, and each connection has a weight. The core of the BP algorithm is to optimize the performance of the network by adjusting these weights [ 20 ]. The input data are normalized to map different dimensions to the same scale to avoid the uneven influence of different features on the results.…”
Section: A Bpnn-hmm-based State Analysis and Processing Model For Spo...mentioning
confidence: 99%
“…Its development meets the demand for energy consumption and optimizes the energy consumption structure (He et al, 2022;Li, 2022;Liu, 2023). By utilizing shale gas, carbon emissions can be reduced, effectively mitigating climate warming (Wang, 2022;Cai, 2023;Hu et al, 2023;Liu and Guo, 2023). China possesses the world's largest reserves of technologically recoverable shale gas, accounting for 15% of the global total (Li et al, 2022a;Zhang K. et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%